2015
DOI: 10.1016/j.jmarsys.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of hypoxia frequency changes in the northern Adriatic Sea during the period 1972–2012

Abstract: Hypoxia events frequently occurred in the bottom layer of the northern Adriatic Sea (NAd) from midsummer to mid-autumn, when the water column is highly stratified, with highly variable spatial extent and duration. To determine the mechanisms of changes in hypoxia frequency and their relation to environmental conditions, 40 yr-long time series of dissolved oxygen and of parameters that describe freshwater influence, stratification processes, and circulation patterns were analysed. It was shown that seasonal hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 50 publications
(78 reference statements)
4
53
0
Order By: Relevance
“…The present-day FML thickness of at least 16 cm and the signs of deeper incomplete mixing at the Po prodelta (with high density of shrimp mounds on the seafloor) can reflect a renewal in bioturbation in the earliest twentyfirst century. This renewal is suggested by the decline in TOC in sediment cores, probably reflecting the lower frequency of hypoxia directly observed since the 1990s in the northern Adriatic Sea (Djakovac et al 2015). At Panzano, stratigraphic changes in stratification cannot be detected due to slower sedimentation rate and because flood events do not reach such magnitude as at the Po prodelta.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The present-day FML thickness of at least 16 cm and the signs of deeper incomplete mixing at the Po prodelta (with high density of shrimp mounds on the seafloor) can reflect a renewal in bioturbation in the earliest twentyfirst century. This renewal is suggested by the decline in TOC in sediment cores, probably reflecting the lower frequency of hypoxia directly observed since the 1990s in the northern Adriatic Sea (Djakovac et al 2015). At Panzano, stratigraphic changes in stratification cannot be detected due to slower sedimentation rate and because flood events do not reach such magnitude as at the Po prodelta.…”
Section: Discussionmentioning
confidence: 97%
“…Although there are methodological differences with later surveys, they can provide order-of-magnitude information on C. gibba abundance in the early twentieth century. Minimum monthly concentrations of bottom-water dissolved oxygen for the NW Adriatic for the years 1911-1984 were extracted from the western sector of Justić et al (1987) and for the years 1972-2012 from stations SJ101 and SJ108 of Djakovac et al (2015) (Fig. 2C).…”
Section: Setting Andmentioning
confidence: 99%
“…Overall, both satellite-derived and in situ-derived sea surface temperature trends reach their maximum values in summer (June-July), while they are lowest in October and January-February. Such large temperature trends in the northern Adriatic and in the examined period might be due to (1) much shallower thermocline in the northern Adriatic than in the rest of the Adriatic and Mediterranean (Franco et al, 1992;Artegiani et al, 1997;Lipizer et al, 2014), resulting in a larger accumulation of heat energy near the surface, and (2) a consequence of atmospheric teleconnection processes acting on a larger spatial and temporal scale, like the Atlantic Multidecadal Oscillation (AMO; Knight et al, 2006), which has been found to be responsible for half of the sea surface temperature trend in the Mediterranean (Marullo et al, 2011;Skliris et al, 2012;Macias et al, 2013). Regarding the rest of the Adriatic, the literature implies that sea surface temperature had a negative trend in the coastal eastern Adriatic between 1960 and 1975, while this trend was strongly positive between 1979 and 2015 (0.23-0.32 • C over 10 years; Grbec et al, 2018).…”
Section: Trendsmentioning
confidence: 94%
“…This indicates a weakening of the stratification south of the Po River delta and implies that these higher-than-average temperature bottom trends might be due to an increase of heat transfer towards the bottom in the area. Temperature trends are lowest on the eastern section of the transect (0.1-0.2 • C over 10 years), where an inflow of waters from the middle Adriatic occurs (Franco et al, 1992;Orlić et al, 1992;Artegiani et al, 1997).…”
Section: Trendsmentioning
confidence: 97%
See 1 more Smart Citation